Sediment characteristics of mangrove areas of brackishwater impoundments - Manjappa, H; Gowda, G; Rajesh, K M; Mridula, R M (Indian Journal of Fisheries, 2011)
Sediment chloride, pH, organic carbon, texture and phycio-chemical characteristics of the overlying water in the mangrove, non mangrove and wood logging areas of brackish water impoundment along Nethravathi estuary have been studied. The mangrove areas and wood logging area recorded lower mean temperature and pH and higher organic carbon contents as compared to non mangrove areas. Wood logging area recorded higher fractions of sand during premonsoon and postmonsoon period, higher silt content during monsoon and postmonsoon period and higher clay content during monsoon and premonsoon periods, whereas, at other stations, higher values of sand during post and premonsoon period, silt and clay during monsoon and premonsoon period were noticed.